Development of Flipbook Media Incorporating Responsibility Values for Elementary School Students - Ira Rahmawati; Elan Elan; Erwin Rahayu Saputra (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to design and develop flipbook media that incorporates responsibility values for elementary school students. The study utilized the Design-Based Research (DBR) approach, employing the Reeves model, which consists of four key phases: problem identification and analysis, prototype development, iterative testing and refinement, and reflective evaluation. The study involved fourth-grade students and teachers from elementary schools in Tasikmalaya Regency, West Java, as well as four expert validators specializing in subject content, character education, educational media, and pedagogy. Data were collected through various methods, including observation, interviews, document analysis, questionnaires, and expert evaluations. Both qualitative and quantitative approaches were applied in analyzing the data. The results revealed that the flipbook media incorporating responsibility values is deemed highly appropriate for use in the educational process. Expert evaluations showed that the flipbook media scored high in terms of feasibility, with scores ranging from 75% to 94.90%. The flipbook media was designed with various engaging features, such as videos, games, and visual displays, to foster an active and interactive learning atmosphere